ANALISIS TINGKAT KESUKAAN KONSUMEN TERHADAP ES KRIM PROBIOTIK DENGAN PENAMBAHAN Lactobacillus acidophilus TERENKAPSULASI - Imanuel ' Sianipar; Fajar ' Restuhadi; Yelmira ' Zalfiatri (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
This study aimed the level of consumer likeness based on sensory attributes from five products consist of probiotic ice cream and commercial ice cream. This study was conducted by means of internal and external preference mapping, with the object of research of 5 different types of product samples, consisting of 4 types of probiotic ice cream products and one type of commercial ice cream product, where the product is A0 (non-encapsulated probiotic ice cream), A1 (3%alginate), A2 (4% alginate), A3 (5%alginate) and A4 (Wall's ice cream). The sensory tests conducted washedonic test and descriptive test. The analysis results of AglomerativeHierarchical Cluster (AHC) on hedonic test and Principal Component Analysis (PCA) of descriptive test were then analyzed by Preference Mapping technique. The product selected and most preferred by the consumers is A4 (Wall's ice cream), wherein the A4 product providesthe level of customer satisfaction by 80% with pink colour, mouthfeel (creamy), strawberry aroma, sweet flavor and soft texture.   Keywords: Probiotic Ice Cream, Aglomerative Hierarchical Cluster, Principal Component Analysis, Preference Mapping.